Distinct evolution of charge occupations on Fe 3d orbitals in hole-doped iron arsenic superconductors - Ding, Ming-Cui; Wu, Li-Min; Zhao, Gang; Pan, Bing-Ying; Zhang, Yu-Zhong (Europhysics letters, 2021)
First-principles calculations are performed to study the hole doping effect in a series of iron arsenic superconductors, such as the undoped CaFe 2 As 2 , CaFeAsF, and the hole-doped CaKFe 4 As 4 , KCa 2 Fe 4 As 4 F 2 , and KFe 2 As 2 . Charge occupations in the Fe 3 d orbitals are found to show opposite variations when the filling is changed. Compared with the undoped CaFe 2 As 2 and CaFeAsF, charges of the and orbitals decrease while those of the and d xy orbitals increase in the hole-doped materials CaKFe 4 As 4 , KCa 2 Fe 4 As 4 F 2 and KFe 2 As 2 . By further analyzing the Pauli susceptibilities of CaFe 2 As 2 and CaFeAsF, instability is found at the wave vector of , which is responsible for the stripe type antiferromagnetic order. In contrast, the Pauli susceptibilities of CaKFe 4 As 4 and KCa 2 Fe 4 As 4 F 2 at are strongly suppressed while the instabilities remain around , which may be the origin of superconductivity. Combining with the calculated orbital-resolved Pauli susceptibility, we conclude that hole doping mainly results in a decrease of charge occupations in the and orbitals, and these three orbitals play dominant roles in controlling the magnetic and superconducting properties in these iron-based superconductors.